Arbetspassion : En studie av de tre grundläggande behovens och ledarstilars påverkan på medarbetares arbetspassion - Jakobsson, Maria; Sundberg, Cecilia (2014)
Being motivated is described as having an incentive to do something, either through appreciation of the activity or through the influence of the environment. According to the Self-determination theory employees have three basic psychological needs: competence, autonomy and relatedness that must be in balance for employees to be motivated. Employees can be intrinsic-, extrinsic or unmotivated, where intrinsic motivation is characterized by employees' own inner desire to engage in a work related project. Literature on the subject has shown that when leaders influence employees to achieve goals with extrinsic means, for example with bonus or deadline the employees become external motivated. If an employee value a work related project and also being internally motivated while engaging in it, work passion can develop. Work passion is defined as “a strong inclination toward an activity that people like, that they find important, and in which they invest time and energy.Previous research has shown that employees who experience work passion achieve high performance and well -being. This means that leaders who can create work environments that promote employee´s to find balance in the three basic needs may have employees who experience work passion.The purposes of the study is to develop and test a model by explaining if the three basic needs of self-determination theory can affect passion and if leadership style can influence work passion amongst employee, and if an relation exists between these variables we will explain how. To answer these questions, we have used a quantitative method and chose to look at the empirical data in form of a questionnaire-survey which was send to earlier students at Luleå University of Technology which today are employees in various organisations. The collected material, we analysed in the statistical software SPSS to see if there is a connection between employee's three basic needs and passion, and leadership style and passion.The study shows that when employees have balance within the ...